2021
DOI: 10.1044/2020_jslhr-20-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Hearing Science: Three Memory Systems, Two Approaches, and the Ease of Language Understanding Model

Abstract: Purpose The purpose of this study was to conceptualize the subtle balancing act between language input and prediction (cognitive priming of future input) to achieve understanding of communicated content. When understanding fails, reconstructive postdiction is initiated. Three memory systems play important roles: working memory (WM), episodic long-term memory (ELTM), and semantic long-term memory (SLTM). The axiom of the Ease of Language Understanding (ELU) model is that explicit WM resources are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 108 publications
3
43
0
2
Order By: Relevance
“…Papers 1 and 2 showed that recall performance in the SWIR test was better when noise reduction was activated compared to when it is not in 4T babble, replicating the findings from Ng et al (2013Ng et al ( , 2015. This corroborates evidence that noise reduction facilitates segregation of the target speech from the competing speech, decreasing the need for explicit processing (Rönnberg et al, 2021). Furthermore, in Paper 1 it was shown that the SWIR test with varying list length is sensitive to measuring the cognitive benefit of noise reduction.…”
Section: Main Findings and Conclusionsupporting
confidence: 63%
See 2 more Smart Citations
“…Papers 1 and 2 showed that recall performance in the SWIR test was better when noise reduction was activated compared to when it is not in 4T babble, replicating the findings from Ng et al (2013Ng et al ( , 2015. This corroborates evidence that noise reduction facilitates segregation of the target speech from the competing speech, decreasing the need for explicit processing (Rönnberg et al, 2021). Furthermore, in Paper 1 it was shown that the SWIR test with varying list length is sensitive to measuring the cognitive benefit of noise reduction.…”
Section: Main Findings and Conclusionsupporting
confidence: 63%
“…Although these measures are important, they are not designed to address complaints about listening being effortful even when it is loud enough to be comprehended. Supplementary measures are needed in order for clinicians to understand how cognitive resources are expended during communication and how auditory intervention can support this (Anderson et al, 2018;Pichora-Fuller et al, 2016;Rönnberg et al, 2021).…”
Section: Beyond the Audiogrammentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not find evidence that surprisal, specifically, was tracked differentially by the two age groups (i.e., there was no interaction between age and feature), the overall greater model contributions in the OAs is broadly consistent with the possibility that predictive processes were more actively engaged in that group. Additionally, because audibility-related responses showed prolonged peaks at relatively late latencies (e.g., see peaks at 250-550 ms in Figure 3), we speculate that the tracking of this feature may also reflect utilization of more intelligible speech segments in higher-level processes, such as prospective prediction and retrospective disambiguation and/or error-correction (Rönnberg et al, 2019(Rönnberg et al, , 2021.…”
Section: Possible Mechanisms Of Age-related Amplification Of Speech Trackingmentioning
confidence: 97%
“…The final work and capstone article in this collection was contributed by the conference keynote speaker, Professor Jerker Rönnberg. Dr. Rönnberg would also qualify for an award for the catchiest title in the special section, should one exist, based on his "Three Memory Systems, Two Approaches, and the Ease of Language Understanding Model" (Rönnberg et al, 2021). This brief article is a must-read for those who have not carefully considered cognitive aging and the co-occurring impacts of aging and hearing loss on auditory perception and speech communication.…”
Section: Select Papers From the 8th Aging And Speech Communication Comentioning
confidence: 99%